SesI May Be Associated with the Invasiveness of Staphylococcus epidermidis - Qi, Xiuqin; Jin, Ye; Duan, Jingjing; Hao, Zhihao; Wang, Shanshan; Guo, Yinjuan; Lv, Jingnan; Hu, Longhua; Wang, Liangxing; Yu, Fangyou (Frontiers in Microbiology, 2018)
Staphylococcus epidermidis is a commensal bacterium which widely colonizes in human skin and mucous membrane and rarely causes clinically manifested infections. S. epidermidis surface protein I (SesI) is considered to be the major virulence factor of S. epidermidis infection, but its pathogenesis is not clear. Here, we demonstrate that the prevalence of sesI among S. epidermidis invasive isolates (20.8%, 26/125) was significantly higher than that among colonizing isolates (3.8%, 4/106). The positive rates of biofilm-associated genes (aap, icaA, IS256) and resistance-associated genes mupA among the sesI-positive isolates were significantly higher than those among sesI-negative isolates (p<0.05). And antimicrobial susceptibility testing showed that the resistance rates of sesI-positive isolates to ciprofloxacin, gentamicin and trimethoprim/sulfamethoxazole were significantly higher than those among sesI-negative isolates. Interestingly, 87.8% (21/26) of sesI-positive isolates belong to ST2 determined by MLST, while ST2 was not found among any of the 99 sesI-negative invasive isolates, indicating that there is a strong association between carriage of sesI and ST2 clone. In order to further study the role of sesI gene in pathogenesis, the sesI gene mutant (S. epidermidis RP62AΔsesI) and complementary expression strain (S. epidermidis RP62AΔsesI-C) were successfully constructed. All experimental data indicated that sesI may promote S. epidermidis to adhere and aggregate of S. epidermidis, but it had no obvious effect on the mature stage of biofilm formation. Taken together, these results suggest that sesI, along with antimicrobial and other biofilm-associated genes enables S. epidermidis easier for colonization and adhesion and contributes to the spread of S. epidermidis, especially ST2 clone.